The impacts of COVID-19 on the handling of loads in northeast public ports (Research, Society and Development, 2020)
The COVID-19 pandemic (Sars-Cov-2) brought reflexes and impacts related to public health, but also to various social and economic activities, both public and private. One of these activities is port management, an activity of great importance from the perspective of transport and supply. In this context, the objective of this investigation was to identify the dimension of COVID-19's impact on cargo handling from the 10 largest public ports in the Northeast region of Brazil. For this purpose, bibliographical and documentary sources were used, such as the database of the port sector provided by the National Waterway Transport Agency - ANTAQ. Statistical tests were also applied to verify the history of local port movement between the years 2010 and 2020, with a focus on comparing the period of the pandemic. The analysis identified significant reflexes of the restrictions imposed by the pandemic situation with the decrease in cargo handling in most of the ports studied, but mainly in Aratu/BA, Cabedelo/PB, Fortaleza/CE, Maceió/AL and Recife/PE. On the other hand, it was possible to observe that the Port Contingency Plans had a positive impact on the sector, mitigating other negative effects arising from the COVID-19 pandemic. It is also believed that the plausible legacy of the pandemic crisis runs through the permanent observation of the care recommended by public agencies as opposed to the application of transitional requirements in temporary health crises or various emergencies.